2021
DOI: 10.1016/j.it.2021.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Communication, construction, and fluid control: lymphoid organ fibroblastic reticular cell and conduit networks

Abstract: Fibroblastic reticular cells (FRCs) are a crucial part of the stromal cell infrastructure of secondary lymphoid organs (SLOs). Lymphoid organ fibroblasts form specialized niches for immune cell interactions and thereby govern lymphocyte activation and differentiation. Moreover, FRCs produce and ensheath a network of extracellular matrix (ECM) microfibers called the conduit system. FRCgenerated conduits contribute to fluid and immune cell control by funneling fluids containing antigens and inflammatory mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 107 publications
(179 reference statements)
0
39
0
Order By: Relevance
“…Maturing stromal cells generate chemoattractant gradients that support the separation of lymphocyte niches ( Bénézech et al, 2010 ). The fibroblastic stroma composes an interconnected cellular network, termed the FRC network, which confines a bundled extracellular matrix (ECM) through which lymph fluid from peripheral tissues is filtered ( Acton et al, 2021 ). The unique structure of lymph nodes therefore confers effective communication between peripheral tissues, leukocytes and the stromal cell architecture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maturing stromal cells generate chemoattractant gradients that support the separation of lymphocyte niches ( Bénézech et al, 2010 ). The fibroblastic stroma composes an interconnected cellular network, termed the FRC network, which confines a bundled extracellular matrix (ECM) through which lymph fluid from peripheral tissues is filtered ( Acton et al, 2021 ). The unique structure of lymph nodes therefore confers effective communication between peripheral tissues, leukocytes and the stromal cell architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph nodes constantly filter draining lymph via a conduit network of aligned ECM fibrils ensheathed by FRCs ( Kaldjian et al, 2001 ; Sixt et al, 2005 ). The containment of draining lymph by the FRC network allows for the controlled sensing of soluble mediators from peripheral tissues, but also provides a route to secrete antibodies and other lymphoid tissue-derived molecules out of the lymph node ( Acton et al, 2021 ; Thierry et al, 2018 ). The ECM can also retain chemokines such as CXCL13 to preserve B cells within the follicular region by creating a chemokine gradient ( Cosgrove et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Imaging studies by us and others have demonstrated that drainage of antigens and other soluble mediators from the inoculation site to LNs can happen within several minutes 13,14,99,196‐198 . Upon reaching the lymphatic sinuses, proteins and particles are physically separated based on molecular weight, with smaller antigens (<70 kDa) and fluids entering the LN conduit network distributed throughout the interfollicular regions and the T cell zone 197,199‐202 . These conduits are also directly connected to the nearby blood vessels, and within a few hours, fluid‐borne antigens, cytokines, and chemokines that entered the conduits are rapidly cleared out into the circulation.…”
Section: Information Gradients In the Generation Of Immune Responsesmentioning
confidence: 99%
“…13,14,99,[196][197][198] Upon reaching the lymphatic sinuses, proteins and particles are physically separated based on molecular weight, with smaller antigens (<70 kDa) and fluids entering the LN conduit network distributed throughout the interfollicular regions and the T cell zone. 197,[199][200][201][202] These conduits are also directly connected to the nearby blood vessels, and within a few hours, fluid-borne antigens, cytokines, and chemokines that entered the conduits are rapidly cleared out into the circulation. This can promote deposition of chemokines and inflammatory mediators on the lumen of high endothelial venules and lead to enhanced trafficking of immune cells into the reactive LNs.…”
Section: Informati On G R Ad Ients In the G Ener Ati On Of Immune Re ...mentioning
confidence: 99%
“…One of the first models of a paradigmatic LN was developed to study the 3D spatial cytokine (type I interferon) distribution with a stationary reaction-diffusion model [21]. The development of high-resolution imaging technologies enabled a detailed characterization of the topological and geometrical properties of LN structures, such as the fibroblastic reticular cell network [22], the conduit network [23,24] and the blood capillary network [25][26][27]. The generated quantitative data allowed to proceed with the development of a computational model of the LN geometry to incorporate the conduit and blood vascular networks [28].…”
Section: Introductionmentioning
confidence: 99%